Log in to add a comment

## Answers

We know the formula isĀ .

Therefore the Simple Interest is 900 and the Amonut is 6000+900=6900.

Therefore the Simple Interest is 900 and the Amonut is 6000+900=6900.

Amount at the end of first year=SI+principal

S.I for the second year=p*r*t/100

Amount at the end of second year=SI +principal

SI for the third year=p*r*t/100

Final amount =SI+principal

Compound Interest=(Final Amount-First principal)

amount changes every year.

take amt of first year as the principal for second year

amt of second year as principal for yhird year